Advanced Design and Simulation of Spreader Bar for Safe Lifting of 80 Tons Pressure Vessel by Using Finite Element Analysis - Kusuma, Bagus; Hasibuan, Fardin; Hakim, Arif Rahman; Yulianta, Eka Chandra (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2025)
This study focuses on designing and optimizing a spreader bar for lifting a pressure vessel are 14,214 millimeters in length, 4,364 millimeters in diameter, and a total weight of 80 tons, addressing challenges in load distribution and safety. The spreader bar, constructed from API 5L X52material, was modeled using SolidWorks and analyzed through Finite Element Analysis (FEA) under four lifting configurations. Key parameters such as stress, strain, and displacement were evaluated to ensure compliance with safety standards. Results indicated that all configurations meet the required safety factor of 1.5, with simulation 3 (C-C) demonstrating the best performance in minimizing stress and displacement. The discussion highlights the design's ability to balance structural integrity, material efficiency, and operational safety. The study concluded that the proposed spreader bar design enhances workplace safety, reduces the risk of equipment failure, and provides a cost-effective solution for heavy lifting tasks.